Critical Race Feminism: A Transformative Vision for Service-Learning Engagement - Begum Verjee (The University of Alabama, 2022)
This article explores the development of service-learning from a critical race feminist perspective. Critical race feminism seeks to understand how society organizes itself along intersections of race, gender, class, and other forms of social hierarchies. It utilizes counter-storytelling as methodology and legitimizes the voices of women of colour in speaking about social oppression. Through counter-storytelling, women of colour students, non-academic staff, faculty, and non-university community members relayed their experiences at The University of British Columbia, Vancouver, Canada, which formed the basis for a transformative vision of service-learning engagement. This vision calls for institutional accountability, requiring a critical examination and transformation of hegemonic structures and practices from within before any genuine, respectful, and mutually beneficial relationships with communities of colour can be developed. Such partnerships would enable the university to create outstanding partnerships to address and solve local, national, and global injustices.